A descriptive retrospective study of non-melanoma skin cancers in African patients with albinism at Chris Hani Baragwanath Academic Hospital. July 2015 – June 2017 - Buthelezi, S'lindile Omega (My University, 2020)
Background Oculocutaneous albinism (OCA) is an autosomal recessive genetic disorder characterised by reduced or absent melanin pigment in the skin, eyes and hair. The most serious sequelae are gross visual disturbances and development of skin cancers. Albinism patients develop pre malignant and malignant lesions at an earlier age compared to normal population. Albinos living closer to the equator are at a higher risk of non-melanoma skin cancers. The skin is the largest organ in the human body. It is therefore the commonest site for cancers. The majority of skin cancers are non-melanoma skin cancers, namely basal cell carcinomas (BCC) and squamous cell carcinomas (SCC). They account for 20-30% of neoplasms seen in Caucasians and 1-2% in coloured skin. Chronic sun exposure is the major contributing factor to developing these skin cancers. (Kennedy et al, 2003). Unfortunately the exact prevalence of non-melanoma skin cancers in the South African albinism population is not known. Limited studies have been done in Africa which described the prevalence of skin lesions and skin cancers affecting the albinism population. Objectives Todetermine the number of patients with basal cell carcinomas, squamous cell carcinomas and other non-melanoma skin cancers in both sexes, different age groups, tumour sites in patients with albinism attending Chris Hani Baragwanath Academic Hospital.Methods This study is a retrospective study of laboratory reports of histologically confirmed skin cancers of patients attending Chris Hani Baragwanath Academic Hospital, whose skin biopsy specimens were submitted to the National Health Laboratory Service at Chris Hani Baragwanath Academic Hospital from July 2013 to June 2017. The histology reports provided demographic data and whether the patient has albinism or other risk factors for skin cancers. The report also provided a description of the clinical lesions and site of the lesion. The report also provides a histologic subtype of the skin cancer. Results A total of 50 patients with albinism with confirmed NMSCs on histopathology reports were studied. The study showed a female predominance with 60% patients being female and 40% male. The youngest patient was 19 years old and the oldest was 81 years old. The mean age was 45.44 year and the median age was 43 years from the sample of 50 patients. Out of the 50 patients, 32 patients had Basal cell carcinomas (64%), 26 patients had Squamous cell carcinomas (52%) and 2 patients had Bowens disease (4%). The commonest site was the head and neck region for all types of skin cancers. Conclusion The prevalence of skin cancers in albinism patients is overwhelmingly high. Basal cell carcinomas are predominant over squamous cell carcinomas. Unfortunately there is not enough studies to describe the exact prevalence in South Africa. The last study done in Johannesburg was in 1989. There is still a need to raise awareness and educate African patients on sun protection and sun avoidance as well as early diagnosis and aggressive management of pre malignant lesions.
A research report submitted in partial fulfilment for the requirements of the degree of Master of Dermatology to the Faculty of Health Sciences, University of The Witwatersrand, Johannesburg, 2020